The impact of the introduction of the Euro on firms' expectations concerning export behavior, product innovation and foreign competition - An empirical assessment of the German business-related services sector - Ulrich Kaiser; Claudia Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1998)
This paper analyses the degree to which firms expect to be able to enter new markets, to develop new products and to contend with new foreign competition after the introduction of the Euro. Panel data taken from a quarterly business survey in the service sector are used for the empirical analysis. East German firms do not differ from their West German competitors in their expectations that the Euro will increase export activity and product innovation, but significantly more East German firms expect new foreign competitors to enter the home market. The impact of the Euro on firms' expectations of entering new markets and developing new products is stronger for firms which already export than for those who do not. Further, the degree of preparation for the Euro plays a significant role in firms' market expectations.
Keywords: C21; F14; F15; 330; European Monetary Union; Euro; business-related services; binary probit model; export; foreign competition